Novel Design and Analysis of an Oral Cannabidiol (Cbd) Therapeutic Delivery System for Pain Management - Khan-Flear, Faryal (University of the Witwatersrand, Johannesburg, 2023)
Cannabidiol (CBD) is a non-psychoactive cannabinoid used for its antinociceptive, analgesic and anti-inflammatory properties in chronic pain. The endocannabinoid system (ECS) influences CBD: receptor binding to generate or regulate antinociceptive responses, producing centrally acting analgesia predominantly through Cannabinoid receptor 1 (CB1) abundant in the brain and spinal cord. In contrast, Cannabinoid receptor 2 (CB2) modulates inflammatory responses in immune system cells and tissues. Most oral medications can have inefficient absorption ability and insufficient therapeutic bioavailability due to the solubility of active ingredients and dosage form dissolution. Although the high lipophilicity of CBD enables it to cross the blood-brain barrier (BBB), which prevents the entry of most systematically administered drugs, the oil-soluble CBD is poorly soluble in water, resulting in erratic, incomplete absorption and poor drug bioavailability, preventing therapeutic doses from reaching specific receptors and regions in the brain. Directly ingested CBD also undergoes hepatic and intestinal metabolism, further contributing to therapeutic insufficiencies. Lipid-Based Drug Delivery Systems (LBDDS) can circumvent the drug's hysicochemical properties and the body's protective biological barriers to enhance drug-receptor interaction and elicit a biological response. Lipid combinations in self-emulsifying lipid formulations (SELF) create liposome nanocarriers that entrap and release CBD, providing a non-invasive, transitory, regionally selective delivery method. Nanoliposomes restrict therapeutic delivery to targeted areas, minimizing systemic toxicity and improving drug bioavailability. Manipulating the physical, chemical, and mechanical aspects of nano-liposomes and the material properties of their constituents concerning human anatomy and physiology can help or hinder therapeutic efficiency, drug safety, and delivery. Most therapeutic nanoliposome designs fall within 50–100 nm, facilitating passive transport across the BBB enabling drug receptor binding at brain and spinal cord receptor sites. Modulator uptake and interactions with host cells, enhanced uptake by target cells, and limits accumulation in specific tissues. Nanoliposomes smaller than 100 nm also extend blood circulation by evading renal, hepatic, and immunogenic sequestration and clearance by the mononuclear phagocyte system (MPS), the reticuloendothelial system (RES), opsonization, modulator uptake and interactions with host cells, limited accumulation in specific tissues, low uptake by target cells. This experiment used established system predictors such as HLB and LogP values, Poulton's Lipid Classification System (LCS), Biopharmaceutics Classification System (BCS), Lipinski's Rule of 5 (Ro5), FBDD Rule of 3 (Ro3), Biopharmaceutics Drug Disposition Classification System (BDDCS) to evaluate the critical quality attributes of two optimized formulations able to deliver CBD to the brain and spinal cord. Both formulations consisted of a phospholipid (soy lecithin), unmodified vegetable oils (coconut, olive/castor oil), surfactants (Span 80 and Tween 20), and a cosolvent (ethyl acetate) in the same ratios with the same ingredients, except that the olive oil in one formulation replaced castor oil in the other. These formulations molecularly dispersed CBD in the polymeric matrix of an unstable amorphous solid dispersion (ASD), improving drug solubility and bioavailability compared to crystalline forms. Thermodynamically unstable ASD must be assessed for quality, stability, and resilience to design helpful dosage forms. Both optimized validation batches successfully encapsulated CBD in liposomes in the eutectic ASD mixtures, as reflected in Fourier transform infrared spectroscopy (FTIR) spectrograms and the Differential scanning calorimetry (DSC). The olive oil-containing formulation produced self-micro-emulsifying drug delivery system (SMEDDS). At the same time, the castor oil preparation formed a self-nano-emulsifying drug delivery system (SNEDDS), accounting for the differences in particle size, size distribution, zeta potential, rheology, morphology, drug release and cell culture analysis. The differences arose due to the oils' unique fatty acid composition and chemistry. Drug release test results of each formulation loaded in hydroxypropyl methylcellulose (HPMC) capsules showed good timing for capsule dissolution and a burst release preceding sustained release over 48 hours. Drug release test results established cell viability in culture studies. The positive cell proliferation indicated that the CBD concentrations released by both formulations were non-toxic to mouse embryonic fibroblasts (NIH/3T3) and human embryonic kidney epithelial cell (HEK 293) cultures. Although both formulations yielded favourable results, the analysis indicated that the castor oil formulation was more robust and, therefore, suitable as a nanocarrier for CBD.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirement for the degree of Master of Science in Medicine in the field of Pharmaceutical Affairs (Department of Pharmacy and Pharmacology), in the School of Therapeutic Sciences, in 2023.
Keywords: Cannabidiol (CBD); Endocannabinoid system (ECS); Cannabinoid receptor 1 (CB1); Cannabinoid receptor 2 (CB2); Blood-brain barrier (BBB); Lipid-Based Drug Delivery Systems (LBDDS); Poulton's Lipid Classification System (LCS); Biopharmaceutics Classification System (BCS); Mononuclear phagocyte system (MPS; Reticuloendothelial system (RES); Biopharmaceutics Drug Disposition Classification System (BDDCS); UCTD; SDG-3: Good health and well-being